2005
DOI: 10.4141/s03-086
|View full text |Cite
|
Sign up to set email alerts
|

Gas diffusion and air-filled porosity: Effect of some oversize fragments in growing media

Abstract: Caron, J., Rivière, L.-M. and Guillemain, G. 2005. Gas diffusion and air-filled porosity: Effect of some oversize fragments in growing media. Can. J. Soil Sci. 85: 57-65. Large particles are often added to growing media to improve air-filled porosity, an often-reported growth-limiting factor. Previous studies have shown that large fragments can leave air-filled porosity unchanged and actually decrease the air exchange characteristics in peat:bark and pure peat media, with an adverse effect on plant growth. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 19 publications
1
25
0
1
Order By: Relevance
“…Most D s / D o values in this study (Tables 2–4) were in agreement with those reported in other studies for sandy soils and for similar θ a (Lai et al ., 1976; Jellick & Schnabel, 1986; Shimamura, 1992; Ball et al ., 1994; van Bochove et al ., 1998) and for organic soils (King & Smith, 1987; Caron et al ., 2005). A few values were larger than in other studies.…”
Section: Resultsmentioning
confidence: 99%
“…Most D s / D o values in this study (Tables 2–4) were in agreement with those reported in other studies for sandy soils and for similar θ a (Lai et al ., 1976; Jellick & Schnabel, 1986; Shimamura, 1992; Ball et al ., 1994; van Bochove et al ., 1998) and for organic soils (King & Smith, 1987; Caron et al ., 2005). A few values were larger than in other studies.…”
Section: Resultsmentioning
confidence: 99%
“…Research on growing media has long neglected to consider D s /D o in substrates, relying only on u a , and assuming g to be constant. However, Allaire et al (1996), Caron and Nkongolo (2004), and Caron et al (2005b) showed that g appears to vary considerably at a same u a between different susbtrates . The reason for this is that although large particles improve u a by interacting with adjacent smaller particles to create macropores, they may also create barriers if they are impermeable to gaseous diffusion (Nkongolo and Caron 1999).…”
Section: Methodological Approach Used Tomentioning
confidence: 99%
“…The determination of the oxygen diffusion coefficient played no major role in the analysis of growing media yet [16]. Investigations described in the literature are usually based on mineral soils [4,17].…”
Section: Introductionmentioning
confidence: 99%